Subjective cognitive decline—a neglected but preventable public health concern: development and validation of a risk prediction model for subjective cognitive decline in older adults: a cross-sectional survey study from Anhui Province in eastern China - Liu, Huan; Hu, Xinyu; Liu, Qingwei; Min, Jiahui; Luo, Yang; Dou, Jun-kai; Xu, Qin; Tao, Xiubin; Zhang, Ming (Frontiers in Public Health, 2025)
BackgroundSubjective Cognitive Decline (SCD) is a significant risk factor for dementia and is prevalent among older adults in China. This study aimed to assess the prevalence and associated factors of SCD among older adults in Anhui Province, and to develop a validated risk prediction model.MethodsA cross-sectional study was conducted from July to August 2024 involving 3,124 older adults from Anhui Province. Data were collected using the Subjective Cognitive Decline Questionnaire (SCD-Q9), the FRAIL scale, the Geriatric depression scale-5(GDS-5), the Lubben Social Network Scale-6 (LSNS-6), and the Mini Nutritional Assessment Short Form (MNA-SF). Predictive factors were identified through univariate and multivariate analyses. A logistic regression model was used to identify SCD correlates, and a nomogram was developed. Model performance was evaluated using calibration curves, ROC-AUC, and decision curve analysis (DCA).ResultsThe prevalence of subjective cognitive decline among the older adults in Anhui Province was 69.1% (2,158/3124). Binary logistic regression analysis showed that, 70–79(OR = 1.306, 95% CI 1.081–1.576), and 80-89(OR = 1.434 95% CI 1.054–1.950), have been hospitalized in the past year (OR = 1.424, 95% CI = 1.202–1.686), frail (OR = 2.140, 95% CI = 1.689–2.712), malnutrition (OR = 2.157, 95% CI = 1.806–2.576), depression symptom(OR = 2.500, 95% CI = 2.031–3.077), social isolation (OR = 1.759, 95% CI = 1.420–2.180) were significantly associated with subjective cognitive decline.ConclusionThe developed nomogram provides a reliable tool for predicting SCD risk in older adults, supporting early screening and intervention in clinical practice.